PULSE WAVE DOPPLER ULTRASONOGRAPHY OF THE PANCREAS IN DOGS WITH ACUTE PANCREATITIS - Milastnaia, A. G.; Dukhnytskyi, V. B. (Scientific Progress & Innovations, 2019)
The study describes ultrasonographic methods currently used to assess the condition of dog pancreas. Ultrasonography was the first method that was used in human medicine, and subsequently introduced into veterinary medicine. At present ultrasonography is a method of choice for the evaluation of pancreatic dis-eases and is necessary as a diagnostic method for detecting organ anomalies, especially tumors. Innovative equipment technology has led to the emergence of advanced techniques that complement conventional B-mode ultrasound scanning such as pulse wave Doppler ultrasonography, elastography and high contrast ultrasonography, which enabled for more accurate diagnostics. Blood flow in the basilar and small arteries of the pancreas was studied by color and pulse wave Doppler ultrasonography defining the resistance index and subsequent comparing the data obtained from 80 dogs, clinical signs of acute pancreatitis were ob-served in 70 of them; 10 dogs were clinically healthy and made up the control group. The blood flow in the basilar arterial vessels of the abdominal trunk, the common liver, spleen and mesentery arteries and small vessels of the pancreas in terms of the internal vessel diameter (D, cm), the area of the longitudinal section of the vessel (S, cm²), the contours of the vessel and its involvement in the pathological process. The periph-eral resistance index (Pourcelot, RI – resistance index) was calculated as the ratio of peak systolic and ter-minal diastolic rate difference to peak systolic rate (RI = (Rps – Rtd)/Rps). To determine the index of periph-eral resistance, the quantitative parameters of blood flow were measured, in particular: peak systolic rate (Rps) – the maximum rate of blood flow in the investigated vessel; Rtd – terminal diastolic rate is the maxi-mum rate of blood flow in the investigated vessel at the end of the diastole. The Doppler study provides in-formation on vascular composition and hemodynamics in the blood vessels of different organs. In case of edema form of acute pancreatitis, the resistance index in the major vessels of the abdominal trunk increases by 4–7 % and in the small arteries of the pancreas decreases by 6–8 %. For pancreatic necrosis, the re-sistance index of major vessels increases by 10 % and small arteries of the pancreas decreases by 15–20 %. The prognostic criterion of developing pancreatic necrosis is the detection by the dynamic pulsed-wave Doppler ultrasonography of the unpaired visceral branches of the abdominal aorta with a stable increase in peak systolic blood flow rate by 20 %, the resistance index by 10 % and the resistance index in small arteries of the pancreas decreases by 20 % during the period from 1 to 6 days of starting the disease.